2012
DOI: 10.3390/ph5090925
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cellular and Molecular Effects of Butyrate and Trichostatin A on Vascular Smooth Muscle Cells

Abstract: The histone deacetylase (HDAC) inhibitors, butyrate and trichostatin A (TSA), are epigenetic histone modifiers and proliferation inhibitors by downregulating cyclin D1, a positive cell cycle regulator, and upregulating p21Cip1 and INK family of proteins, negative cell cycle regulators. Our recent study indicated cyclin D1 upregulation in vascular smooth muscle cells (VSMC) that are proliferation-arrested by butyrate. Here we investigate whether cyclin D1 upregulation is a unique response of VSMC to butyrate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 55 publications
(117 reference statements)
4
37
1
Order By: Relevance
“…While systemic inflammation induced by exogenous administration of endotoxin, a product of gram-negative gut microbes, has been shown to exacerbate neointimal hyperplasia after balloon angioplasty (Danenberg et al 2002), a direct correlation between alteration in gut microbial composition and neointimal hyperplasia has not previously been reported. Finally, while other investigators have previously demonstrated that butyrate has anti-proliferative and anti-migratory effects in VSMC (Ranganna and Yatsu 1997;Ranganna et al 2000Ranganna et al , 2003Milton et al 2012;Cantoni et al 2013), the effect of butyrate on the response to arterial injury in vivo has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While systemic inflammation induced by exogenous administration of endotoxin, a product of gram-negative gut microbes, has been shown to exacerbate neointimal hyperplasia after balloon angioplasty (Danenberg et al 2002), a direct correlation between alteration in gut microbial composition and neointimal hyperplasia has not previously been reported. Finally, while other investigators have previously demonstrated that butyrate has anti-proliferative and anti-migratory effects in VSMC (Ranganna and Yatsu 1997;Ranganna et al 2000Ranganna et al , 2003Milton et al 2012;Cantoni et al 2013), the effect of butyrate on the response to arterial injury in vivo has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Milton et al. ; Cantoni et al. ), the effect of butyrate on the response to arterial injury in vivo has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Histone phosphorylation has been shown to globally decrease its chromatin binding affinity 68,69 and TSA has been shown to downregulate several cyclin dependent kinases (CDKs). 70 We decided to analyze two of the most intensively characterized phosphorylation sites to date, S80-P and S421-P. 71 In neurons, S80 is constitutively phosphorylated in the resting state 72 and S421 is phosphorylated in response to neuronal activity. 69 We also decided to include S164-P, a recently described abundant developmental MeCP2 phosphorylation, which has been documented to lower its binding affinity to chromatin.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that trichostatin A, another HDI, also suppresses VSMC proliferation . However, its definite cytotoxicity restricts its application potential . Alternatively, Bur is a naturally occurring short‐chain fatty acid and physiologically exists in the intestinal system and blood.…”
Section: Discussionmentioning
confidence: 99%